Commencement 2010 (Institutional Knowledge at Singapore Management University, 2010)
Guest of honour, Dr Narongchai Akrasanee, former Minister for Commerce and Senator of Thailand, addressing the audience at Singapore Management University's seventh commencement ceremony. The event was held at Resorts World Convention Centre on 21 July 2010.